2009
DOI: 10.1152/ajpcell.00092.2009
|View full text |Cite
|
Sign up to set email alerts
|

Calcium homeostasis in human melanocytes: role of transient receptor potential melastatin 1 (TRPM1) and its regulation by ultraviolet light

Abstract: Transient receptor potential melastatin (TRPM) is a subfamily of ion channels that are involved in sensing taste, ambient temperature, low pH, osmolarity, and chemical ligands. Melastatin 1/TRPM1, the founding member, was originally identified as melanoma metastasis suppressor based on its expression in normal pigment cells in the skin and the eye but not in aggressive, metastasis-competent melanomas. The role of TRPM1 and its regulation in normal melanocytes and in melanoma progression is not understood. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 46 publications
(61 reference statements)
4
77
0
Order By: Relevance
“…Several TRP channels have been proposed to play important roles in the regulation of RMP in certain cell types (11,12). In the present study, analysis of human and monkey colonic SMC revealed TRPC1, C3, C4, C7, M2, M4, M6, M7, V1, and V2 transcript expression.…”
Section: G294supporting
confidence: 51%
“…Several TRP channels have been proposed to play important roles in the regulation of RMP in certain cell types (11,12). In the present study, analysis of human and monkey colonic SMC revealed TRPC1, C3, C4, C7, M2, M4, M6, M7, V1, and V2 transcript expression.…”
Section: G294supporting
confidence: 51%
“…In neonatal human epidermal melanocytes, TRPM1 expression correlates with melanin content, suggesting that TRPM1 is critical to normal melanocyte pigmentation and thus represents a potential target for pigmentation disorders (Oancea et al, 2009;Hughes et al, 2012). TRPM1 regulates pigmentation by controlling melanin synthesis in skin melanocytes (Devi et al, 2009. TRPM2 ( Fig.…”
Section: +mentioning
confidence: 99%
“…Reduced expression of TRPM1 in human melanocytes and mouse melanoma cell lines correlates with decreased melanin content, suggesting that TRPM1-mediated Ca 2+ homeostasis plays a role in the regulation of melanogenesis (Devi et al 2009;Oancea et al 2009). Interestingly, another group reported that human melanocytes express mGluR6, but not Goα, and that TRPM1 activity in human melanocytes is positively regulated by the mGluR6 signaling pathway (Devi et al 2013).…”
Section: Application Of Another G-protein Subunit Gβγ Did Not Supprmentioning
confidence: 99%